Pengaruh Model Permainan Tradisional Bentengan Terhadap Hasil Belajar Gerak Dasar Lokomotor Pada Siswa Kelas V Sdn Duri Utara 04 Petang Jakarta Barat - Syifa Fauzia; Bayu Thomi Rizal; Khavisa Pranata; Asruddin Asruddin (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The purpose of this study was to evaluate whether the use of learning models in the Bentengan Traditional Game of class V SDN in Duri Utara 04 Petang has a significant impact on the achievement of student learning outcomes in PJOK subjects. Especially in understanding Basic Locomotor Movements. This research method utilises a quantitative approach with a Quasi Experimental Design in the form of Post Test-Only Control Design. Grade V students from one of the public elementary schools in West Jakarta City became the research sample. The sample was selected using the Random Sampling method. Point Biserial correlation was conducted to test the validity of 40 items, it was found that 25 items were valid, while 15 items were invalid (dropped). While in the Reliability Test, the Alpha Cornbach formula was used, obtained = 0.818> 0.381 = then the data is categorised or qualified as "Reliable". Furthermore, the Liliefors Test was carried out for the Normality Test in the V-A experiment class obtained <, namely 0.128 < 0.193 and the results of the normality test calculation in the V-B control class <, namely 0.133 < 0.188, so the data was categorised or qualified as "Normal". While the Fisher Test is used to calculate the homogeneity test obtained < stated that the two classes are experiment and control categorised or qualified "Homogeneous". After applying the t-test to test the hypothesis, the results obtained were 6.972 with 2.019 at the level (? = 0.05) stated = rejected, which means that there is a significant effect on learning using the Bentengan Traditional Game learning model on the Learning Outcomes of Physical Education class V at SDN Duri Utara 04 Petang.